LA TRANSFUSION DE MEDULA EN ALGUNOS ESTADOS INFECCIOSOS - SANCHEZ YLLADES; CASTILLO (Secretaria Salubridad, CD MEXICO, DF, MEX, 1943)
The author reports a total of 2352 biopsy prepns made by aspiration, with 1742 (76%) positive for some type of tumor He points out the advantages of such a method of diagnosis, such as the avoidance of spread of malignant tumors which sometimes results
REV MEX MED
Keywords: TRANSFUSION, MEDULA, ESTADOS, INFECCIOSOS; CIENCIAS MEDICAS; MEDICINA INTERNA; HEMATOLOGIA